Analisis Keamanan Jaringan Komputer Berbasis Routerboard Mikrotik Rb941 dengan Metode Extended Access List Pada SMK Negeri 1 Stabat - Eva Agus Pratiwi; Desti Putri Rahayu; Priska Ayu Syahputri; Popi Melita; Sumarlin; Surizar Rahmi Danur (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
Security in computer networks is very important to monitor network access and prevent unauthorized misuse of network resources. The task of network security is to protect and prevent it from causing system losses and damage to computer networks. One aspect of computer network security is to use the Extended Access List method, which is a type of Access Control List (ACL), which is an appropriate security method for network communications. The Extended Access List plays a role in managing the access rights of each host in a network simulation. The Extended Access List can filter network data traffic by controlling whether packets are forwarded or stopped. The Extended Access List can also guarantee computer security so that communication lines and access rights for each computer can work properly. With the Extended Access List method, it is hoped that it can monitor network access and prevent unauthorized misuse of network resources.